2016
DOI: 10.1039/c6fo00856a
|View full text |Cite
|
Sign up to set email alerts
|

Dietary resistant starch type 4-derived butyrate attenuates nuclear factor-kappa-B1 through modulation of histone H3 trimethylation at lysine 27

Abstract: Indigestible resistant starches (RS) are substrates for gut-microbial metabolism and have been shown to attenuate intestinal inflammation but the supporting evidence is inconsistent and lacks mechanistic explanation. We have recently reported dietary RS type 4 (RS4) induced improvements in immunometabolic functions in humans and a concomitant increase in butyrogenic gut-bacteria. Since inflammation is a key component in metabolic diseases, here we investigated the effects of RS4-derived butyrate on epigenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…As a type of soluble fibre, resistant starch (RS) has been reported to decrease large intestinal inflammation by down-regulating the expression of inflammatory mediators, such as pro-inflammatory TNF- α and NF- κ B ( 1 , 9 ) , and enhancing the expression of nuclear transcription factor PPAR- γ ( 10 ) . In being resistant to digestion by mammalian enzymes in the small intestine, RS is highly fermentable for amylolytic bacteria in the hindgut ( 11 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a type of soluble fibre, resistant starch (RS) has been reported to decrease large intestinal inflammation by down-regulating the expression of inflammatory mediators, such as pro-inflammatory TNF- α and NF- κ B ( 1 , 9 ) , and enhancing the expression of nuclear transcription factor PPAR- γ ( 10 ) . In being resistant to digestion by mammalian enzymes in the small intestine, RS is highly fermentable for amylolytic bacteria in the hindgut ( 11 ) .…”
mentioning
confidence: 99%
“…In being resistant to digestion by mammalian enzymes in the small intestine, RS is highly fermentable for amylolytic bacteria in the hindgut ( 11 ) . The beneficial effect of RS on host physiology may, therefore, encompass SCFA-derived attenuation of intestinal inflammation ( 1 , 9 , 12 ) . For the five RS types, most evidence for immunomodulatory abilities exists for RS2 (granular and high amylose starches) and RS3 (retrograded starch) ( 1 , 10 ) , whereas less has been reported about anti-inflammatory properties of RS4 ( 1 , 9 ) .…”
mentioning
confidence: 99%
“…It is generally accepted that inflammation-related molecules and pathways are useful targets for the prevention and treatment of cancer [ 23 , 24 , 25 ]. Furthermore, dietary factors can modulate in vivo epigenetic signatures and, therefore, susceptibility to diseases [ 5 , 26 ]. Of particular interest, in the context of inflammatory gene expression modulation by dietary agents is the tri-methylation of H3 at lysine 27 (H3K27me3), which is frequently associated with transcriptional repression and gene silencing [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction, purification, cDNA synthesis and real-time PCR were performed as previously described by our group [ 5 , 26 ]. All samples were run in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, when Foxp3 is acetylated, the transcription factor becomes more stable and has greater propensity to bind DNA yielding a more stable and effective Treg population [182]. In addition to the regulation of Treg differentiation, butyrate has also been shown to increase the tri-methylation of lysine 27 on histone 3 (H3K27me3) in the promoter of nuclear factor-κB1 (NF-κB1) in colon tissue resulting in repression of inflammation [183]. In our lupus mouse studies, we found a marked depletion of lactobacilli in our lupus animals and increases in Lachnospiraceae compared to age-matched health controls.…”
Section: Treg-th17 Balancementioning
confidence: 99%